1948
DOI: 10.1111/j.1476-5381.1948.tb00377.x
|View full text |Cite
|
Sign up to set email alerts
|

Diamidines as Antibacterial Compounds

Abstract: Study of the diamidines was first directed to MATERIALS AND METHODS protozoal diseases, their usefulness in bacterial infections being discovered subsequently; some of Antibacterial activity our early results on propamidine were cited byOrganisms.-These were derived mainly from the Thrower and Valentine (1943), and its value in Lister Institute

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1948
1948
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…A similar latency period in the antibacterial action of diamidines, was attributed to cellular penetration time (8). The prolonged S ânciif.z/Ercoli latency period (up to 48 h) in the advanced infection, besides a larger absolute number of more resistant organisms in an increased popula tion, depends probably also on sensitivity variations in the different reproductive phases of the parasite.…”
Section: Discussionmentioning
confidence: 80%
“…A similar latency period in the antibacterial action of diamidines, was attributed to cellular penetration time (8). The prolonged S ânciif.z/Ercoli latency period (up to 48 h) in the advanced infection, besides a larger absolute number of more resistant organisms in an increased popula tion, depends probably also on sensitivity variations in the different reproductive phases of the parasite.…”
Section: Discussionmentioning
confidence: 80%
“…The cationic nature of these compounds has led to an explanation of their mode of action on the basis of competition with hydrogen ions for vital enzyme positions (Browning, Gulbransen, and Kennaway, 1919;Elson, 1945;Albert et al, 1945;Massart et al, 1947b). On the basis of the observed inhibitions of respiration by acridines (Silverman, Ceithaml, Taliaferro, and Evans, 1944;Ferguson and Thorne, 1946;Massart et al, 1947a;Deley, Peeters, and Massart, 1947;Marshall, 1948a) and by diamidines (Bernheim, 1943;Marshall, 1948b;Wien, Harrison, and Freeman, 1948), the negatively charged enzyme protein for which the drug cation and hydrogen ions compete is probably the dissociating acidic group of a respiratory enzyme. Quastel and Wheatley (1931) have suggested that the dehydrogenase system is primarily of an acidic nature on the basis that basic dyes inhibited and the acidic dyes did not inhibit the dehydrogenase activity.…”
Section: Discussionmentioning
confidence: 99%
“…66 Acquired resistance of S. aureus to propamidine and of S. pyogenes to dibromopropamidine have been demonstrated. 67,68 In each case, there was cross-resistance to other diamidines but not to penicillin or PF.…”
Section: Other Antibacterial Agentsmentioning
confidence: 97%